4CPS-199 Introducing a clinical pharmacist to a care of the elderly (coe) day hospital. (2nd March 2018) - Carroll, J; Curran, C; Donegan, C; Williams, D; Cushen, AM; Doyle, N
Abstract : Background: Medication review is an essential part of comprehensive geriatric care, and is a primary function of the clinical pharmacist (CP). A new CP service has been established in a Care of the Elderly (COE) Day Hospital with the aim of improving outcomes from medication use. The CP service centres on medication review and patient education. Purpose: To develop a clinical pharmacy service in the day hospital to improve the quality of pharmaceutical care provided to care of the elderly patients. Material and methods: Data from the first 3 months of the service were collected prospectively to measure the quantity and type of CP interventions. The potential clinical outcome of each intervention was assessed by the day hospital CP and a gerontology SpR using a validated visual analogue scale (0–10, 0 representing no potential effect and 10 representing death). The frequency with which advised changes were acted upon by the treating doctor was also recorded. Results: One hundred and ninety-five patients (mean 81 years, age range 58–98 years) were reviewed during 33 clinic days. A current medication list was obtained for all patients and an average of 1.8 pharmaceutical care interventions were identified per patient. Of these 340 interventions, the medical team or patient agreed with 54%, 39% were not accepted and 6% had an unknown outcome. The interventions were classified according to type as follows: 18% actual or potential adverse reaction, 14% each for supratherapeutic dose and untreated indication, 11% subtherapeutic dose and 10% each for improper administration, drug without indication and education provided to the patient. The clinical significance mean scores were categorised as leading potentially to minor harm (<3)=10%, moderate harm (3–7)=89% and severe harm (>7)=1%. Good agreement was observed between the two assessors (Pearson correlation coefficient=0.97). Conclusion: CP medication usage review in the day hospital has resulted in a positive contribution to the care of elderly patients. Opportunities to improve visibility of the service will be explored. No conflict of interest